1991
DOI: 10.1007/bf00500385
|View full text |Cite
|
Sign up to set email alerts
|

Plasma islet amyloid polypeptide (Amylin) levels and their responses to oral glucose in Type 2 (non-insulin-dependent) diabetic patients

Abstract: Fasting plasma islet amyloid polypeptide concentrations and their responses to an oral glucose load were determined in non-diabetic control subjects and patients with abnormal glucose tolerance in relation to the responses of insulin or C-peptide. Plasma islet amyloid polypeptide was measured by radioimmunoassay. In the non-diabetic control subjects, fasting plasma islet amyloid polypeptide was 6.4 +/- 0.5 fmol/ml (mean +/- SEM) and was about 1/7 less in molar basis than in insulin. The fasting islet amyloid p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
91
2
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(104 citation statements)
references
References 9 publications
9
91
2
1
Order By: Relevance
“…In the normal subjects, fasting circulating IAPP was approximately 4 pmol/l, which is in the range of 2-10 pmol/l found in previous studies in healthy subjects (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)21). Furthermore, in the normal subjects, there was a close correlation between circulating IAPP and circulating insulin in the fasting state, the regression coefficient being 0.74, which confirms previous studies (7,12,14).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In the normal subjects, fasting circulating IAPP was approximately 4 pmol/l, which is in the range of 2-10 pmol/l found in previous studies in healthy subjects (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)21). Furthermore, in the normal subjects, there was a close correlation between circulating IAPP and circulating insulin in the fasting state, the regression coefficient being 0.74, which confirms previous studies (7,12,14).…”
Section: Discussionsupporting
confidence: 89%
“…IAPP is co-stored with insulin in the pancreatic B cells and previous studies have shown that IAPP and insulin are co-released under a variety of experimental conditions (7)(8)(9)(10)(11)(12)(13)(14)(15)(16). However, it has also been suggested that under certain conditions IAPP and insulin are released in a non-parallel fashion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IAPP is colocalised with insulin in the secretory granules of islet fl-cells and co-secreted in response to fl-cell secretagogues [3,4]. IAPP has been identified in all species examined so far [5] and, in common with other secretory peptides, is synthesized as a larger precursor molecule.…”
Section: Introductionmentioning
confidence: 99%
“…Amylin has been shown to mirror insulin secretion in healthy subjects [5], obese subjects, prediabetics (subjects with impaired glucose tolerance) [6,7], and patients with Type 2 Diabetes [5]. These findings suggest an active role for plasma amylin levels in modulating glucose metabolism [8]. However, the mechanisms and the precise role of amylin in the pathophysiology of Type 2 Diabetes remains unclear.…”
Section: Introductionmentioning
confidence: 99%